Care Descriptions at Work: Textual Technologies from the Standpoint of Care Workers - Lundberg, Kjetil G. (Journal of Comparative Social Work, 2019)
Forms and documents play significant roles in the context of care work for older people. One type of form that care workers use on a daily basis is individual care descriptions (ICDs). An ICD is a text that is written on a piece of paper or on a computer, and specifies the care tasks to be carried out. How do ICDs operate in local settings of care work for older people? Anchored in insights from institutional ethnography, I investigate care work practices from the standpoint of care workers in care settings in Norway. In the empirical analysis, I identify and pay attention to two particular ICDs and how they enter the everyday care work practices. The findings indicate that ICDs contribute to standardizing care work practices that are related to changes in the cultural and institutional foundations of the welfare state. Furthermore, ICDs coordinate practices in different ways, and promote several forms of coordination. Hence, when analysing care descriptions at work, awareness of contextual sensitivity is called for. This paper contributes to research on management and power relationships in home care and nursing care work by illustrating different dimensions of textually based coordination.